Analisis Peran Ulasan Konsumen dalam Membangun Kepercayaan terhadap Brand di Platform E-Commerce Indonesia - Annisa Bilkhisti; Hopkyn Lumbanbatu; Seyla Ratna Sari Simanjuntak; Melani Simanjuntak (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of consumer reviews in building brand trust on e-commerce platforms in Indonesia, where online transactions rely heavily on digital information. Consumer reviews function not only as sources of product evaluation but also as signals that reduce perceived risk and uncertainty in online shopping environments. Using a quantitative approach, this research analyzes how review quality, credibility, and valence influence consumer trust toward brands. The findings indicate that informative, credible, and experience-based reviews significantly strengthen brand trust, which subsequently affects purchase intention and repeat buying behavior. Trust emerges as a mediating factor that connects online reviews with consumer decision-making processes. Furthermore, the study highlights that the accumulation of consistent reviews contributes to long-term brand equity in digital marketplaces. These results reinforce the importance of strategic review management for e-commerce businesses aiming to maintain competitiveness and customer loyalty. The study provides practical implications for brand managers in optimizing review features as part of relationship-building efforts with consumers in the Indonesian e-commerce context.